Կոոպերատիվների համաշխարհային փորձը և ԼՂՀ-ում գյուղատնտեսական կոոպերատիվների ստեղծման, զազգացման հնարավորությունները - Բեգլարյան, Ի.
На современном этапе кооперация представляет собой перспективное направление, способное обеспечить развитие агропромышленного комплекса республики. Одновременно представлен опыт Западной Европы, США и возможности, созданные в НКР, на основе которых сделан вывод о том, что кооперация может стать оптимальным способом, содействующим эффективному использованию производственных ресурсов аграрной сферы и улучшению социально-экономического положения населения. Currently cooperative movement is regarded as a futuristic direction, which allows to secure the development of agricultural production system in the Republic. At the same time the article presents the experience of Western Europe, USA and the opportunities created in NKR on the basis of which a conclusion is drawn that cooperation may become the best way supporting to the effective use of production resouces of the agrarian sector and improvement of the social-economic conditions of the population.
Keywords: Հողաշինարարություն